SN 2023ixf: Interaction signatures in the spectrum at 445 days - Folatelli, Gastón; Ferrari, Lucía; Ertini, Keila; Kuncarayakti, Hanindyo; Maeda, Keiichi (EDP Sciences, 2025)
Context. SN 2023ixf is one of the nearest and brightest Type II supernovae (SNe) of the past decades. Its proximity and extremely early discovery have enabled a large number of studies based on extensive observations throughout the electromagnetic spectrum. A rich set of pre-explosion data provided important insight into the properties of the progenitor star. There has been, however, a wide range of estimated initial masses of 9–22 M⊙. Early monitoring of the SN also showed the presence of a dense circumstellar material (CSM) structure near the star (≲1015 cm), which was probably expelled in the last years prior to the explosion. At farther distances, there have been indications of a drop in the CSM density. These extended CSM structures can be further probed with late-time observations during the nebular phase.
Aims. We monitored the spectroscopic evolution of SN 2023ixf at late phases with the aim of characterizing the progenitor properties. The observations also serve to search for indications of ejecta–CSM interaction that may shed light on the mass-loss processes during the final stages of evolution of the progenitor star.
Methods. This study is based on a nebular spectrum obtained with GMOS at the Gemini North Telescope 445 days after explosion. The SN evolution was analyzed in comparison with a previous spectrum at an age of 259 days. The 445 d spectrum was further compared with those of similar SNe II and with synthetic radiation-transfer nebular spectra. Line profiles were used to determine properties of the emitting regions. [O I] and [Ca II] line fluxes were used to derive an estimate of the progenitor mass at birth.
Results. The 445 d spectrum exhibits a dramatic evolution with signs of ejecta–CSM interaction. The Hα profile shows a complex profile that can be separated into a boxy component, possibly arising from the interaction with a CSM shell and a centrally peaked component that may be due to the radioactive-powered SN ejecta. The CSM shell would be located at a distance of ∼1016 cm from the progenitor, and it may be associated with mass loss occurring up until ≈500−1000 years before the explosion. Similar interaction signatures have been detected in other SNe II, although for events with standard plateau durations, this occurred later than 600–700 days. SN 2023ixf appears to belong to a group of SNe II with short plateaus or linear light curves that develop interaction features before ≈500 days. Other lines, such as those from [O I] and [Ca II], appear to be unaffected by the CSM interaction. This allowed us to estimate an initial progenitor mass, which falls in the relatively low range of 10–15 M⊙.